Structural health monitoring of different geometry structures with optical fiber sensors - Antunes, P. (2012)
In this paper, we describe the structural health monitoring of several structures, with different geometry, materials and behaviors, using optical fiber sensors. Those studies aimed to demonstrate the feasibility of such technologies in structural health monitoring, with all the advantages inherent to the optical fiber technology.